Adaptação transcultural e avaliação das propriedades de medida do questionário Knowledge of Disease Management-cf-adolescents para indivíduos com fibrose cística - Hilda Angélica Iturriaga Jimenez (2022)
Cystic Fibrosis (CF) is an autosomal recessive genetic disease caused by a mutation in the gene on chromosome 7, which affects all exocrine glands. Since the diagnosis of the CF, which is usually made early, still in childhood, both parents and patients are informed about the course of the disease and the care they should take throughout their lives, to avoid complications that could lead to early death. Thus, in the early stages of the disease, patient care is performed by parents or proxies, but over the years, patients have to acquire autonomy to manage their treatment. Based upon this, it is necessary to measure the knowledge acquired by patients, considering that knowledge is an important form of intervention in CF, which may lead to the prevention of complications. Therefore, the objective of this thesis was to cross-culturally adapt the Knowledge of Disease Management-CF-Adolescent (KDM-CF-Adolescent) questionnaire to the Brazilian-Portuguese language, as well as to test its measurement properties. Two steps were carried out: 1) initial translation, synthesis of translations, back-translation, expert committee evaluation, and testing of the pre-final version, following standardized procedures 2) application of the questionnaire to Brazilian patients with CF, between 11 and 20 years of age, to assess its measurement properties. The application of the questionnaire was carried-out online, using the Google Forms platform, due to the COVID-19 pandemic and social isolation measures. Descriptive statistics (means, standard deviations and frequencies) were used to describe the sample. Data were submitted to Rasch analysis, which allows for assessing the quality of the responses according to a probabilistic model, in which the probability of choosing an answer depends only on the individual's ability and the difficulty of the item. The analysis was performed using the WINSTEPS software (version 5.2.2.0) and various aspects of measurement properties were verified. Thirty-five individuals (23 men) were included. They had a mean age of 15.73.1 years, ranging from 11 to 20 years. After applying the translated version of the KDM-CF-Adolescent questionnaire, no needed to adjust or changes to the items was identified to enable their understanding. The KDM-CF-Adolescent divided the sample into two levels ok knowledge and the items into three levels of difficulty, leading to person and item reliability indices of 0.67 and 0.81, respectively and internal consistency of 0.69. All KDM-CF items fit the expectations of the Rasch model, since all infit/outfit values and associated z values were within the expected range. The principal component analysis of the residuals confirmed the existence of two dimensions, separating the scale into two groups of items. However, they did not function as independent scales. There was no duplication of any content, that is the answer to one item did not interfere with the answer to another. There were not found any floor and/or ceiling effects. Therefore, the Brazilian-Portuguese version of KDM-SF Adolescent questionnaire demonstrated satisfactory measurement properties to be used within clinical and research contexts to measure the knowledge of adolescents with CF.